Distance Learning and Character Building in Rural Area During the Covid-19 Pandemic - I Putu Mas Dewantara; I Ketut Dibia (Universitas Pendidikan Ganesha, 2021)
The COVID-19 pandemic has brought a number of obstacles and challenges in learning. The bigger obstacle is found for schools in rural areas. Starting from the problem of the availability of supporting facilities, parental support, to the problem of teacher readiness in carrying out learning and character education during the COVID-19 pandemic. Therefore this study aims to describe the teacher's strategy in carrying out distance learning and character education in rural area during the Covid-19 pandemic. This research was a qualitative research, involving 13 teachers. The data were collected through observation, interview, and questionnaire. The data analysis was carried out in by using a qualitative descriptive analysis. The data were analyzed through three stages, namely data reduction, data presentation, and data verification. The data were validated through source, method, and theory triangulations. The results of this study indicate that the teachers’ strategies in implementing distance learning include: Whatsapp-based online distance learning, offline distance learning, and mixed distance learning. There were 3 strategies to carry out character education during the Covid-19 pandemic, namely direct feedback through examples or narrative in the text. Examples given were also in the form of pictures; and through a checklist of daily and weekly activities. Various obstacles occured in distance learning and character education. Parents also felt stressed because of the increased burden during the pandemic. Therefore, collaboration between various components is needed to design the most effective learning strategies in rural areas.